DE LA TELEVISIÓN DE PAGO AL VIDEO BAJO DEMANDA. ANÁLISIS DE LA PRIMERA TEMPORADA DE LA ESTRATEGIA DE PRODUCCIÓN ORIGINAL DE FICCIÓN DE MOVISTAR+ - Dra. Concepción CASCAJOSA VIRINO (Fonseca, Journal of Communication, 2023)
The article analyzes the first season of the original fiction strategy by the pay-TV platform Movistar+. Although it was announced at the end of 2014, its first series was not released until September 2017, which was followed by seven more series until June 2018. The research is based on a double hypothesis. First, this strategy of original fiction showed the transformation of the traditional model of pay-TV into a new model of distribution focused on videoon-demand. Second, this transformation was made seeking to as-sociate the Movistar+ brand with values related to difference and quality. The examination of the eight series released in this period allows us to observe the transformation of the production model of pay television in search of a personalized consumption.